2014
DOI: 10.1016/j.bbr.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated prostacyclin biosynthesis in mice impacts memory and anxiety-like behavior

Abstract: Prostacyclin is an endogenous lipid metabolite with properties of vasodilation and anti-platelet aggregation. While the effects of prostacyclin on the vascular protection have been well-documented, the role of this eicosanoid in the central nervous system has not been extensively studied. Recently, a transgenic mouse containing a hybrid enzyme, of cyclooxygenase-1 linked to prostacyclin synthase, was developed that produces elevated levels of prostacyclin in vivo. The goal of this study was to investigate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…In an open field assessment of locomotor activity, both of the amyloid-expressing lines (APdE9 and APdE9/CP-Tg), displayed hyperactivity when compared to the CP-Tg or NTg controls at 12 months of age. CP-Tg mice exhibited decreased activity and spent a larger amount of time along the margin of the field, similar to findings from our previous work (46). Notably, PGI2 overexpression, alone and with the APdE9 phenotype, significantly improved coordination by the last two rotarod trials.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In an open field assessment of locomotor activity, both of the amyloid-expressing lines (APdE9 and APdE9/CP-Tg), displayed hyperactivity when compared to the CP-Tg or NTg controls at 12 months of age. CP-Tg mice exhibited decreased activity and spent a larger amount of time along the margin of the field, similar to findings from our previous work (46). Notably, PGI2 overexpression, alone and with the APdE9 phenotype, significantly improved coordination by the last two rotarod trials.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, PGI2 appears to impact influence behavior and cognitive processing positively; CP-Tg mice contain a modified cyclooxygenase-1 enzyme linked to Prostaglandin E synthase, which increases PGI2 production (43)(44)(45). In our previous work, we found that increased levels of PGI2 improved short-term memory as the CP-Tg mice learned significantly faster in training compared to controls in a contextual fear conditioning test (46).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Here, with comprehensive experiments and more data, we demonstrated that the transgenic mouse model exhibited marked resistance to vascular assault through induced carotid arterial blockage, induced acute thrombotic stroke and arterial arrest, and angiotensin-induced peripheral vasoconstriction. The safety of the engineered trans-gene, COX-1-10aa-PGIS (integrated COX-1 and PGIS activities together in a single polypeptide chain) was confirmed by healthy animal development and maintenance of a longer lifespan with improved mental performance, which has been demonstrated in a previous publication 16 . It greatly increased the possibility of correcting inherited heart diseases using emerging gene medicine, such as the transgene, COX-1-10aa-PGIS, at the current experimental level.…”
Section: Introductionsupporting
confidence: 58%
“…More recently, Vollert et al . found that increased levels of prostacyclin decreased anxiety‐like behaviour and improved learning in the fear‐conditioning memory test. Interestingly, it was also found that the reported effect differed according to the age of the subjects, with prostacyclin producing an anxiogenic effect in young mice and an anxiolytic effect in older animals.…”
Section: Fatty Acid‐derived Hormonesmentioning
confidence: 94%